Dinamika Sosial Ekonomi Masyarakat Kampung Baso Kabupaten Mamberamo Raya di Era Otonomi Khusus - Loppies, Megiridha (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
This study aims to analyze the socio-economic dynamics of the Baso Village, Mamberamo Raya Regency, Papua in special Autonomy era. Special Autonomy was expected to bring positive changes to the lives of the Papuan people, especially in improving social and economic welfare. This study uses a historical method consisting of the following stages: heuristics, source criticism, interpretation and historiography. The results of the study indicate that the dynamics of social development still include quantitative developments such as improving education and health infrastructure. However, the improved infrastructure is still inadequate. Meanwhile, in terms of quality, educated and trained education and health workers are still very lacking. The economic dynamics of the Baso Village community still depend on traditional agriculture and fisheries. Special Autonomy has provided support through development and empowerment programs, but optimal management of natural resources has not been fully achieved. Although Special Autonomy has had a positive impact on the social and economic dynamics in Baso Village, more intensive efforts are still needed to maximize the potential of natural resources and overcome infrastructure challenges in order to achieve better community welfare in the future